Learning Behavior in Using Portal System for Architecture’s Students in the Research Methodology Course - Nurakmal, Abdullah@ Goh Tuo Ho; Norngainy, Mohd Tawil; Mazlan, Mohd Tahir; Azami, Zaharim; Che-Ani, A. I. (Maxwell Scientific Organization, 2012)
E-learning is one approached in the learning style of the courses for UKM Bachelor of Architecture program, namely Research Methodology. The e-learning is not a new paradigm in today’s teaching and learning process, thus, using the platform of UKM portal system, SPIN we start to adapt this approach and make it as practical to the students. This study is highlighting 4 learning approaches that might be preferred by the students in encouraging them to use SPIN, namely class contact hours of every 2 weeks time, 1 h lecture, white board style and let the student talk and do. The findings from the study reveals, in principal the students agree to use the SPIN, with the lecturer observing the usage of the system in SPIN via progress monitoring report and correlate the total time, numbers of visit and page hits of the students. High total time does not guarantee the student is an active SPIN user. Nevertheless the study also found that there is a cheater in this system.